2005
DOI: 10.1211/jpp.57.10.0009
|View full text |Cite
|
Sign up to set email alerts
|

Transporter-mediated influx and efflux mechanisms of pitavastatin, a new inhibitor of HMG-CoA reductase

Abstract: The purpose of this study was to gain a better understanding of the transport mechanism of pitavastatin, a novel synthetic HMG-CoA reductase inhibitor. Experiments were performed using oocytes of Xenopus laevis expressing several solute carrier (SLC) transporters and recombinant membrane vesicles expressing several human ABC transporters. The acid form of pitavastatin was shown to be a substrate for human OATP1, OATP2, OATP8, OAT3 and NTCP, and for rat Oatp1 and Oatp4 with relatively low K(m) values. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 30 publications
(27 reference statements)
3
60
0
Order By: Relevance
“…The International Transporter Consortium recently suggested that possible OATP inhibition by new molecular entities should be tested using a prototypical substrate such as estradiol-17␤-glucuronide (Giacomini et al, 2010). However, we showed that OATP1B3-mediated uptake of estradiol-17␤-glucuronide was not affected by EGCG, whereas uptake of Fluo-3 was inhibited and uptake of estrone-3-sulfate was stimulated (Fig.…”
Section: Effect Of Green Tea Catechins On Oatp Functionmentioning
confidence: 69%
See 1 more Smart Citation
“…The International Transporter Consortium recently suggested that possible OATP inhibition by new molecular entities should be tested using a prototypical substrate such as estradiol-17␤-glucuronide (Giacomini et al, 2010). However, we showed that OATP1B3-mediated uptake of estradiol-17␤-glucuronide was not affected by EGCG, whereas uptake of Fluo-3 was inhibited and uptake of estrone-3-sulfate was stimulated (Fig.…”
Section: Effect Of Green Tea Catechins On Oatp Functionmentioning
confidence: 69%
“…Given that OATP1A2 is expressed in enterocytes, our results suggest that OATP1A2 could be involved in the absorption of ECG and EGCG from the gut. Furthermore, given that OATP1A2 can transport numerous drugs including fexofenadine (Cvetkovic et al, 1999), several antibiotics such as levofloxacin (Maeda et al, 2007), methotrexate (Badagnani et al, 2006), statins (Fujino et al, 2005;Ho et al, 2006), and talinolol (Shirasaka et al, 2010), there is the potential for fooddrug interactions such as the ones described for fruit juices (Dresser et al, 2002;Lilja et al, 2004;Greenblatt, 2009) in patients that complement their prescription drugs with over-the-counter green tea supplements. A similar danger may exist for OATP1B3.…”
Section: Effect Of Green Tea Catechins On Oatp Functionmentioning
confidence: 99%
“…Of all the mechanisms of sinusoidal transport, the organic anion transporting polypeptides (OATPs) are believed to be the most relevant for hepatic uptake of many anionic drugs. In addition to OATPs, The sodium-dependent taurocholate co-transporting polypeptide-mediated transport has been shown to contribute to the hepatic uptake of statins (79)(80)(81)(82). The ability to predict uptake clearance and determine the contribution of individual transporters to overall hepatic uptake is therefore critical in assessing the potential pharmacokinetic and pharmacodynamic variability associated with drug-drug interactions and pharmacogenetics.…”
Section: Examples Of Quantitative Targeted Proteomics For Membrane Trmentioning
confidence: 99%
“…Although reports vary, atorvastatin, lovastatin, pitavastatin, and simvastatin have been implicated as CLInICAL StAteMentS AnD GUIDeLIneS both P-gp substrates and inhibitors. [15][16][17][18][19] Common P-gp substrates, inducers, and inhibitors that affect statin metabolism are given in Table 3. 12,16,[20][21][22] Other transport proteins, including organic aniontransporting polyprotein (OATP) 1B1 (OATP1B1) and efflux transporter breast cancer resistance protein, are involved in statin uptake and metabolism.…”
mentioning
confidence: 99%